Study on fatty acid composition and physico-chemical properties of Nyctanthes arbortristis root - Rahman, Mohammad Mizanur; Shahjahan, Mohammad (Journal of the Bangladesh Chemical Society, 2012)
Fatty acid composition of Nyctanthes arbortristis Linn root extracted successively with light petroleum ether (40-600C bp.)- n-hexane and chloroform were analyzed by gas liquid chromatography (GLC). Twenty one fatty acids were identified in the Seuli root. The major saturated and unsaturated fatty acids are palmitic acid (C16:0, 13.97%) and oleic acid (C18:1, 28.43%). Physio-chemical characteristics, such as iodine value, moisture, ash, lignin and crude fibre of the Seuli root were also determined. Keywords: Nyctanthes arbortristis Linn; Seuli; root; fatty acid composition; gas liquid chromatography. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9709 Journal of Bangladesh Chemical Society, Vol. 24(2), 202-208, 2011